Religious Studies as Neoliberal "Triple Mediation": Toward a Deconstruction of Its "Colonial Difference" - Raschke, Carl A. (Religions, 2019)
This article makes the case, citing the work of David Chidester, Achille Mbembe, Tomoko Masuzawa, and Walter Mignolo, that the academic study of religion (often known as "religious studies" in the Anglophone world, Religionswissenschften or sciences religieuses in Continental Europe) remains both historically, and to a large extent contemporaneously, a "colonial" discipline derived from what Michel Foucault termed the structures of "power/knowledge", imposed on the cognitive and philosophical traditions of non-Western and indigenous peoples. It argues that the "archetype" of rationality taken for granted in much Western scholarship about "religion" amounts to what Chidester terms a "triple mediation" between the imperial domination and colonial classification and administration of subjugated peoples and their symbolical practices and cultural memory-one which, in fact, has been re-inscribed in present day "neoliberal" fantasies of one world "without religion". Finally, the article proposes a new "deconstructive" reading of theories of religion using post-structuralist instead of Enlightenment methodologies.